Mississippi swindle : Brett Favre and the welfare scandal that shocked America - White, Shad (Steerforth Press, 2024)
"This riveting exposé tells the story of a small group of people who misappropriated and misdirected federal money intended for some of the poorest inhabitants of our nation's poorest state in a sprawling conspiracy that stretched from Mississippi to Malibu. Over many years, well-connected donors, highly placed officials, and popular public figures diverted tens of millions of dollars from the federal government's TANF -- temporary assistance for needy families -- program until a Republican auditor, his small team of dedicated investigators, and a Democratic prosecutor joined forces to stop them. Peopled with unforgettable characters -- from the perpetrators; to the impoverished citizens for whom the money was intended; to the investigators, prosecutors, and reporters who held them to account -- this captivating white collar true crime drama is also a cautionary tale about the possibility for similar frauds in all fifty states"--Jacket.